1982
DOI: 10.1056/nejm198209023071002
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Amantadine and Rimantadine in the Prophylaxis of Influenza a Infection

Abstract: Four hundred fifty volunteers participated in a placebo-controlled, double-blind, randomized trial of the prophylactic effects of rimantadine and amantadine during an outbreak of influenza A. The subjects received drugs orally at a dose of 100 mg twice a day for six weeks. Influenza-like illness occurred in 41 per cent of the subjects receiving placebo but in only 14 per cent of those receiving rimantadine and 9 per cent of these receiving amantadine (P less than 0.001 for either drug vs. placebo). Laboratory-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
237
0
2

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 467 publications
(242 citation statements)
references
References 16 publications
2
237
0
2
Order By: Relevance
“…Amantadine is a tricyclic amine exhibiting antiviral activity against influenza A [8][9][10] and other viruses including some flaviviridae 11,12 to which HCV belongs. Whereas its mechanism(s) of action against influenza A is well characterized, 13 that against other viruses remains ill defined.…”
Section: H Epatitis C Virus (Hcv) Infection Follows a Chronic Coursementioning
confidence: 99%
“…Amantadine is a tricyclic amine exhibiting antiviral activity against influenza A [8][9][10] and other viruses including some flaviviridae 11,12 to which HCV belongs. Whereas its mechanism(s) of action against influenza A is well characterized, 13 that against other viruses remains ill defined.…”
Section: H Epatitis C Virus (Hcv) Infection Follows a Chronic Coursementioning
confidence: 99%
“…antiviral compounds | murine lethal-infection model | neuraminidase T o treat influenza, which causes respiratory disease with significant morbidity and mortality especially among the elderly and young (1), the M2 ion channel blockers (aminoadamantanes: amantadine and rimantadine) have been used for more than two decades (2,3). However, aminoadamantane-resistant viruses, which readily arise (4,5), limit the efficacy of these drugs.…”
mentioning
confidence: 99%
“…It has been reported that 1-aminoadamantane hydrochloride (marketed as Symmetrel) is effective in the prevention and treatment of the influenza (A) virus (Hoffmann, 1973;Dolin et al, 1982;Bright et al, 2005). However recent studies suggest that the virus is becoming increasingly resistant to this anti-influenza drug (Betakova, 2007).…”
Section: S1 Commentmentioning
confidence: 99%
“…For applications of adamantane-ammonium salts in virology, see: Hoffmann (1973); Dolin et al (1982); Bright et al (2005); Betakova (2007). For applications of amines for the capture of CO 2 from the atmosphere, see : Yang et al (2008).…”
Section: Related Literaturementioning
confidence: 99%